Stochastische Simulation zur Werkzeuglebensdaueroptimierung und Präzisionsfertigung in der Kaltmassivumformung - Völkl, Ralf (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2008)
In cold forging the scatter of process parameters like workpiece material flow stress can show a high effect on the process properties e.g. tool life or workpiece accuracy. This book presents a simulation based method of modelling the influence of parameter scatter end using the model to optimize process design. In several case studies the potential of the method to increase tool life and workpiece accuracy is demonstrate